The Economic Dimension Of Environmental Risk Management in Knowledge-Based Society - Ana-Maria DINU (Revista Română de Statistică, 2014)
Environmental risk for the majority of companies is the deterioration of bottom-line performance from: increased regulation on energy usage, eroded reputation, brand name and market share from an environmental incident, increased operating costs from the effects of global warming, higher fuel costs as natural resources are depleted and loss of market share to more environmentally “savvy” competitors with marketing campaigns which portray social responsibility.